Sierra Gorda 013: Unusual CBa‐like chondrite. (4th March 2022) - Ivanova, Marina A.; Lorenz, Cyril A.; Humayun, Munir; Yang, Shuying; Ma, Chi; Teplyakova, Svetlana N.; Franchi, Ian A.; Korochantsev, Alexander V.
Abstract: The new metal‐enriched anomalous chondrite Sierra Gorda 013 (SG 013) contains two different lithologies. Lithology 1 (L1) is represented by anomalous CBa‐like chondrite material containing 80 vol% of Fe, Ni‐metal particles and globules up to 6 mm in size; chondrules and clasts of types POP, BO, and SO (up to 5 mm in diameter); rare sulfides; and shock melted silicate–metal areas. It does not contain any fine‐grained matrix. Several chondrules contain chromite–pyroxene symplectites. Lithology 2 (L2) has a recrystallized texture with evenly distributed olivine, pyroxene and plagioclase. L2 does not have any chondrules or sulfides, and contains less Fe, Ni‐ metal ( 25 vol%) than L1. Both lithologies contain reduced olivine (Fa2–4) and pyroxene (Fs3.5), similar to CBa chondrites. Similar to CBa, there is no Ni‐Co correlation in the SG 013 metal. Rare sulfides in L1 are enriched in V. Chromite was observed in both lithologies. Oxygen isotope compositions of both lithologies are different but in the range of CBa chondrites. Bulk major and trace element geochemistry of nonporphyritic chondrules and bulk siderophile compositions in metal globules of L1 indicate elemental fractionation during formation of metallic and silicate objects with records of the evaporation process: depletion in moderate and volatile elements with the exception of Cr. Bulk geochemistry of porphyritic chondrules of L1 and the silicate portion of L2 is similar and also indicates evaporation processes. The rare Earth element (REE) distribution of L1 chondrules records a very fractionated signature corresponding to possible differentiated precursor material, while the REE pattern of L2 is primitive chondritic. The formation of SG 013 could be explained by collisions of planetesimals producing an impact plume, the precursor material of which could be chondritic and possibly differentiated. Both lithologies were affected by secondary processes: L1 preserved the traces of shock events and partial melting resulting in formation of symplectites in chondrules, melt pockets, and metal–silicate melt between the metal globules; L2 was affected by shock thermal metamorphism (up to 900 °C) resulting in recrystallization.